LINGUISTIC FEATURES OF ENGLISH ADVERTISING SLOGANS IN EDUCATIONAL SERVICES - Abdurakhmanova Sarvinoz Orifjon qyzy (International Journal of Literature and Language Studies, 2026)
This article examines the linguistic characteristics of English-language advertising slogans in the educational sector. Based on a corpus of 50 slogans from leading international universities and educational platforms (2023–2025), the study identifies lexical, stylistic, and syntactic patterns that distinguish educational advertising from commercial consumer advertising. The findings reveal a predominance of lexical fields related to "future and career prospects" (31.25%), "transformation and personal development" (26%), and "uniqueness and excellence" (22%). Syntactic analysis shows a dominance of imperative sentences (40%) and narrative constructions (32%), with an average sentence length of 5.4 words, confirming the principle of syntactic compression. Stylistic devices, including personalization (30%), metaphor (14%), and parallelism (8%), enhance emotional impact and memorability. The study contributes to understanding how intangible educational services are linguistically represented and offers practical implications for copywriting in educational marketing.